2010
DOI: 10.1007/s10750-010-0512-4
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and chemical preservatives alter the stable isotope values of carbon and nitrogen of the Asiatic clam (Corbicula fluminea)

Abstract: International audienceWe tested the impacts of most common sample preservation methods used for aquatic sample materials on the stable isotope ratios of carbon and nitrogen in clams, a typical baseline indicator organism for many aquatic food web studies utilising stable isotope analysis (SIA). In addition to common chemical preservatives ethanol and formalin, we also assessed the potential impacts of freezing on δ¹³C and δ¹⁵N values and compared the preserved samples against freshly dried and analysed samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 20 publications
4
46
2
Order By: Relevance
“…The reported isotopic shift is typically small (within 2%) and comparable with the isotopic shifts observed in ecosystem reconstruction using the isotopic signatures of archived sample material (Pruell et al 2003;Solomon et al 2008;Wainright et al 1993). Previous studies have shown that the effects of preservation on stable isotopes depend on organisms and preservatives and are often inconsistent and variable (Barrow et al 2008;Kelly et al 2006;Schmidt et al 2009;Syvaranta et al 2008Syvaranta et al , 2010. These methodological inconsistencies inhibit our ability to appropriately pool data across studies and may adversely affect data interpretation within studies.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The reported isotopic shift is typically small (within 2%) and comparable with the isotopic shifts observed in ecosystem reconstruction using the isotopic signatures of archived sample material (Pruell et al 2003;Solomon et al 2008;Wainright et al 1993). Previous studies have shown that the effects of preservation on stable isotopes depend on organisms and preservatives and are often inconsistent and variable (Barrow et al 2008;Kelly et al 2006;Schmidt et al 2009;Syvaranta et al 2008Syvaranta et al , 2010. These methodological inconsistencies inhibit our ability to appropriately pool data across studies and may adversely affect data interpretation within studies.…”
Section: Introductionmentioning
confidence: 58%
“…(e.g., Arrington and Winemiller 2002;Barrow et al 2008;Syvaranta et al 2008Syvaranta et al , 2010Ventura and Jeppesen 2009). Our results show that the d 13 C values of every fish species preserved in formalin were depleted with an average about -1% relative to their controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feuchtmayr and Grey 2003;Carabel et al 2009;Syväranta et al 2011). Although these shifts appear less pronounced than they are for 13 C (Bosley and Wainwright 1999;Kaehler and Pakhomov 2001), they are important to consider as 15 N can elucidate the trophic relationships or identify the ecological niche occupied by an organism (consumer) within a food web Epstein 1978, 1981;Post 2002;Wallace et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Lovelock 1957;Jiang et al 1987;Wroblowski et al 1996). This idea is supported by evidence of protein denaturation in a range of Wsh (Mackie 1993;Paredi et al 2010), cephalopod (Paredi et al 2006;Reyes et al 2009) and bivalve species (Makri 2010;Syväranta et al 2011). What is clear, however, is that although freezing is often considered the preferred method of sample preservation for isotope studies, it is not a panacea and the assumptions of no preservation eVect of freezing should not be taken for granted.…”
Section: Discussionmentioning
confidence: 99%